Israiliyyat Dalam Tafsir Al Khathib Asy-Syarbini - Fery Rahmawan Asma (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
This article aims to reveal various israiliyyat data contained in the interpretation of Tafsir as-Siraj al-Munir by Muhammad asy-Syarbini, then analyzed comparatively with the views of other commentators. Therefore, the method that the author uses in this study is a qualitative method, it aims to be able to find out what israiliyyat material that ash-Syarbini mentions in his interpretation, what steps are taken in mentioning it as well as his response related to these stories and his relationship with the commentators before his time related to the story of israiliyyat. From the results of this study, the author succeeded in mapping the information system of the story mentioned by the author of the commentary, the views of scholars regarding these stories and the attitude of the author of the interpretation in commenting on israiliyyat as well as the roots of the views of asy-Syarbini.